119. Cortical excitability in patients affected by brain tumors. Issue 1 (January 2015) - Maggio, R.; Marino, M.; Allegra, C.; Terranova, C.; Rizzo, V.; Girlanda, P.; Quartarone, A.
<x xml:space="preserve">Abstract</x> In this study we investigated cortical excitability, inhibitory and excitatory intracortical circuitries, by using transcranial magnetic stimulation, in both hemispheres of patients affected by brain tumors. Cortical excitability was probed with transcranial magnetic stimulation in 10 right-handed patients (3 women), aged 49–70 years (mean age: 54.8 years) and 10 age-matched healthy controls. We tested motor thresholds (MT), motor evoked potential (MEP) recruitment curve, cortical silent period (CSP), short and long intracortical inhibition (SICI and LICI), intracortical facilitation (ICF), short and long afferent inhibition (SAI and LAI) and inter-hemispheric inhibition (IHI). RMT and AMT were higher in both hemispheres of patients with brain tumors than healthy controls. The slope of MEP recruitment curve was deeper in both hemispheres of patients with brain tumors. SICI, LICI, SAI and LAI are reduced in patients with brain tumors compared with aged matched healthy controls. Cortical excitability, specially inhibitory intracortical circuitries, are impaired in both hemispheres of patients affected by brain tumors.